2012
DOI: 10.1183/09059180.00005111
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention: exposure reduction, skin exposure and respiratory protection

Abstract: Interventions for the primary prevention of occupational asthma have been reported in the medical literature, understanding the effectiveness of these efforts could help future interventions. The aim of our study was to evaluate the existing knowledge regarding the impact of controlling work exposure on the prevention of occupational asthma. We conducted systematic literature searches through April 2010 to examine if control of workplace exposures is effective for primary prevention of sensitisation and occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 96 publications
0
62
0
5
Order By: Relevance
“…There was no statistically significant difference between respirators, but none of the workers who wore the fullface respirators developed occupational asthma, even those who worked in high-exposure jobs. More detailed comments to individual statements are provided by HEEDERIK et al [161].…”
Section: Strong Moderatementioning
confidence: 99%
“…There was no statistically significant difference between respirators, but none of the workers who wore the fullface respirators developed occupational asthma, even those who worked in high-exposure jobs. More detailed comments to individual statements are provided by HEEDERIK et al [161].…”
Section: Strong Moderatementioning
confidence: 99%
“…The June 2012 issue contained a series of articles written by members of an ERS task force on the management of workrelated asthma [11][12][13][14][15], which provided vital background and context to the main summary document, published in the ERJ [16]. The success of this joint venture will hopefully act as a model for future task forces.…”
mentioning
confidence: 99%
“…Animal studies have demonstrated that dermal exposure to sensitisers can elicit respiratory inflammation after airway challenge [30]. Case reports and limited epidemiological studies (primarily isocyanates) support this concept [31]. Moreover, several common occupational contact allergens can also potentially cause occupational asthma [32].…”
mentioning
confidence: 99%